Moral Norm and Theory of Planned Behavior: The Intention to Use Eco-Friendly Reusable Bag - Ayu Ekasari; Syeliya Md Zaini (Indonesian Journal of Sustainability Accounting and Management, 2020)
This study analyzes the influence of three variables in the theory of planned behavior (TPB) along with the moral norm variable to predict pro-environmental behavior, specifically the use of eco-friendly reusable bags. The sample population in this study was 280 people who were aware of the existence of eco-friendly reusable bags and understood its use. Data were analyzed using structural equation modeling. The results of hypothesis testing showed a positive influence of moral norm, attitude, and perceived behavioral control on the intention to use eco-friendly reusable bags. However, the influence of subjective norms on the intention to use eco-friendly reusable bags was found to be negative. This is a pioneering research in the use of the expanded TPB model with the moral norm variable to predict the use of eco-friendly reusable bags, a behavior that is rarely studied. As is well-known, the TPB has been widely used in explaining pro-environmental behavior; however, studies that include the moral norm variable are scarce. The results of the study suggest that decision-makers and retailers need to design social advertisements that can encourage consumers to use eco-friendly reusable bags that would minimize the use of plastic bags.